DOI: 10.1007/978-3-540-79590-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Microactuator Design Using Surface Acoustic Wave Devices

Abstract: An integration of low power operated Surface Acoustic Wave (SAW) devices with the electrostatic microactuators for microfluidic and similar applications is presented in this chapter. Passive, low power, and small area devices can be interrogated wirelessly using SAW devices, which can respond to a uniquely coded signal for a secure and reliable operation. The novel approach relies on converting the interrogating coded signal to surface acoustic wave that is then correlated with an embedded code. A theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This analysis is an extended version of the authors' previous work [20], which was developed to analyse the performance of a SAW device based electrostatic actuator using the Rayleigh-Ritz method. Here, an energy minimization technique is used to solve the problem for the corrugated diaphragm model.…”
Section: The Rayleigh-ritz Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis is an extended version of the authors' previous work [20], which was developed to analyse the performance of a SAW device based electrostatic actuator using the Rayleigh-Ritz method. Here, an energy minimization technique is used to solve the problem for the corrugated diaphragm model.…”
Section: The Rayleigh-ritz Methodsmentioning
confidence: 99%
“…In the authors' previous work [19,20], the electric potential at the output IDT region was found to be a combination of the electric potential at the IDT fingers and the electric potential at the IDT finger gaps, and this is shown in equation (2). where…”
Section: Electrostatic Force Generationmentioning
confidence: 98%
“…Passive actuation mechanisms eliminate the need for active circuitry and batteries and are thus potentially advantageous in terms of size, longevity, cost and robustness of the devices. Passively operated wireless microactuators have been reported to use several mechanisms, including electrostatic actuations induced by surface acoustic waves [12] and magnetic fields [13], magnetic actuations [14][15][16][17], energy-beam-assisted heating (for shape-memory alloys (SMA) [18][19][20][21] and bimorph [22][23][24]). However, they pose various practical issues such as small actuation force and stroke, use of high voltages, micromachining and integration of ferromagnetic materials, and actuator/system packaging.…”
Section: Introductionmentioning
confidence: 99%